A transformation grammar for housing rehabilitation - Eloy, S. (2011)
Existing housing stock must be rehabilitated to meet the new needs of dwellers in the current information society. Consequently, Information and Communications and Automation Technologies (ICAT) must be integrated in living areas. Both shape grammar and space syntax can be used as tools to identify and encode the principles and rules behind the adaptation of existing houses to new requirements. The research proceeds by first identifying the dwellers' demands and determine how the use of technology influences them. The second step is to identify the functional, spatial, and constructive transformations performed manually by human designers in order to infer the corresponding transformation rules and encode them into a grammar. The third step aims to test the grammar in other dwellings that are part of the corpus of the study.